Clinical Experience with COVID-19 at a Specialty Orthopedic Hospital Converted to a Pandemic Overflow Field Hospital. (November 2020) - Miller, Andy O.; Kapadia, Milan; Kirksey, Meghan A.; Sandhu, Milan; Jannat-Khah, Deanna; Bui, Trang; Boyle, K. Keely; Krez, Alexandra; Russell, Linda; O'Neill, Jennifer; Stein, Emily M.; Henry, Michael W.; et al.
Background: COVID-19, the illness caused by the novel coronavirus, SARS-CoV-2, has sickened millions and killed hundreds of thousands as of June 2020. New York City was affected gravely. Our hospital, a specialty orthopedic hospital unaccustomed to large volumes of patients with life-threatening respiratory infections, underwent rapid adaptation to care for COVID-19 patients in response to emergency surge conditions at neighboring hospitals. Purposes: We sought to determine the attributes, pharmacologic and other treatments, and clinical course in the cohort of patients with COVID-19 who were admitted to our hospital at the height of the pandemic in April 2020 in New York City. Methods: We conducted a retrospective observational cohort study of all patients admitted between April 1 and April 21, 2020, who had a diagnosis of COVID-19. Data were gathered from the electronic health record and by manual chart abstraction. Results: Of the 148 patients admitted with COVID-19 (mean age, 62 years), ten patients died. There were no deaths among non-critically ill patients transferred from other hospitals, while 26% of those with critical illness died. A subset of COVID-19 patients was admitted for orthopedic and medical conditions other than COVID-19, and some of these patients required intensive care and ventilatory support. Conclusion: Professional and organizational flexibility during pandemic conditions allowed a specialty orthopedic hospital to provide excellent care in a global public health emergency.